An investigation of underground monitoring and communication system based on radio waves attenuation using ZigBee - Moridi, Mohammad; Kawamura, Youhei; Sharifzadeh, Mostafa; Chanda, E.; Jang, Hyongdoo (Pergamon, 2014)
In the challenging environment and changing topology of a mine, reliable and effective communication is a high-stake issue along with the objectives of safe and efficient mining operations. Automation by remote and automatic systems have improved workplace health and safety for employees, cost-effectiveness, management of technical problems, energy saving, real-time response to events. In response to these challenges, wireless sensor networks (WSNs) have been widely employed in underground monitoring and communication systems for the purpose of environmental monitoring, positioning of workers and equipment, operational monitoring and communication system. Considering the capabilities of WSNs, ZigBee network is adapted. In this study, common WSNs are evaluated for application in underground mines and demonstrated why ZigBee network performance is suitable for such environments. ZigBee radio waves attenuation is investigated to evaluate stable communication range between ZigBee nodes at straight and curved tunnels in a real mine scenario. Moreover, experimental measurements of ZigBee radio waves attenuation are validated by simulation results. Based on the analysis of the experimental and simulation results, the effective factors on the radio waves attenuation in the junctions, curvatures and fields near and far from the source are assessed. Finally, stable wireless communication ranges between developed ZigBee nodes in the underground Angas Zinc Mine is concluded 100 m and 70 m for straight and curved tunnels, respectively. The development of ZigBee network application compared to other WSNs in underground mines is also approved.